HPLC and UHPLC for practicing scientists - Dong, M. W., 1949- (Wiley, 2019)
"Many things have changed in HPLC in the last ten years since the publication of the first edition. First and foremost is the advent of UHPLC (ultra-high-pressure liquid chromatography) and the conttinuing migration of HPLC to UHPLC, the modern standard platform. Since UHPLC is an improved and higher-performance HPLC platform based on the same chromatographic theories. they share many commonalities such as columns and instrument modules. The 2nd edition, therefore, includes a substantial overview of all the fundamentals and practice of HPLC to include updates on UHPLC. There are three new chapters: UHPLC (standalone chapter on concepts, benefits, practice, and limitations), LC/MS, and the analysis of recombinant biologics particularly monoclonal antibodies (mAbs) used as therapeutics. While all chapters are revised in the new edition, five chapters are mostly rewritten including HPLC columns, instrumentation, pharmaceutical analysis, method development, and regulatory aspects"--
Originally published: Modern HPLC for practicing scientists. 2006
Keywords: vysokoúčinná kapalinová chromatografie; léky -- analýza; high performance liquid chromatography; drugs -- analysis; příručky; handbooks and manuals